Phonological Development in a Kurdish-Speaking Child: A Longitudinal Case Study. - Fatemi-Syadar, Shahla; Zarifian, Talieh; Modarresi, Yahya (Journal of Monolingual & Bilingual Speech (JMBS), 2026)
The purpose of the current longitudinal case report study was to document and investigate the phonological acquisition in one typically developing Kurdish-speaking boy during 10 months between the ages of 21 and 31 months. Speech samples were analyzed to document phonological acquisition, phonological accuracy, phonetic inventory, phonological mean length of utterance (PMLU), the proportion of whole-word proximity (PWP), the proportion of whole-word correctness (PWC), error patterns, syllabic shapes, consonant clusters acquisition, and speech intelligibility. All Kurdish vowels and consonants except trilled /r/ were acquired in a phonetic inventory by 31 months. He also acquired consonant clusters in the initial and final syllable position and produced all Kurdish syllable structures. The child's speech intelligibility increased over time. As anticipated, his phonological processes decreased over time but still continued to an older age. This study provides longitudinal information that can be implemented to demonstrate individual differences between children in the evaluation and treatment of Kurdish-speaking children.